Preventing inappropriate signals pre- and post-ligand perception by a toggle switch mechanism of ERECTA - Liangliang Chen; Michal Maes; Alicia M. Cochran; Julian R. Avila; Paul Derbyshire; Jan Sklenar; Kelsey M. Haas; Judit Villén; Frank L.H. Menke; Keiko U. Torii (Proceedings of the National Academy of Sciences, 2025)
Dynamic control of signaling events requires swift regulation of receptors at an active state. By focusing on the Arabidopsis ERECTA (ER) receptor kinase, which perceives peptide ligands to control multiple developmental processes, we report a mechanism preventing inappropriate receptor activity. The ER C-terminal tail (ER_CT) functions as an autoinhibitory domain: Its removal confers higher kinase activity and hyperactivity during inflorescence and stomatal development. ER_CT is required for the binding of a receptor kinase inhibitor, BKI1, and two U-box E3 ligases, PUB30 and PUB31, that trigger activated ER to degradation through ubiquitination. We further identify ER_CT as a phosphodomain transphosphorylated by the coreceptor BAK1. The phosphorylation impacts the tail structure, likely releasing ER from autoinhibition. The phosphonull version enhances BKI1 association, whereas the phosphomimetic version promotes PUB30/31 association. Thus, ER_CT acts as an off–on–off toggle switch, facilitating the release of BKI1 inhibition, enabling signal activation, and swiftly turning over the receptors afterward. Our results elucidate a mechanism that fine-tunes receptor signaling via a phosphoswitch module, maintaining the receptor at a low basal state while ensuring robust yet transient activation upon ligand perception.